Testing of Several Paper Types as Insulators for Electric Power Systems - Marganda Harliman Siagian; T Haryono; Bambang Sugiyantoro (IJITEE (International Journal of Information Technology and Electrical Engineering), 2019)
Abstract— This research was based on high voltage equipment failure due to an increase in temperature and humidity on insulating materials. This can cause the power system reliability to decrease. On the other hand, paper is frequently found and used in everyday life. Paper can be categorized as a solid insulator even tough its use in the electric power system can be considered as minimum. This paper aimed to determine electrical insulation characteristics of three types of paper on market and to determine the amount of failed voltage and leakage current of test materials included with other factors such as temperature rise effect as well as humidity conditions in sample testing. The employed test samples were photo paper, duplex paper, and samson craft paper with a length of 7 cm and width of 7 cm with different thickness for each paper type. Tests were carried out with two paper conditions, i.e. paper was soaked in Shell Diala B oil and was not soaked in Shell Diala B oil, so that the significance of the oil on the paper used as an ingredient in testing could be known. The test results showed that temperature and humidity affected dielectric strength magnitude and test sample leakage current value. In addition, it was also found that test sample result impregnated with Shell Diala B had a higher dielectric magnitude compared to the unimpregnated test sample. Test samples impregnated with Shell Diala B oil had a leakage current value which tended to be smaller than the unimpregnated test sample.